Exploring diastolic pressure ratio to fractional flow reserve discordance and a hypothesis on tailoring diastolic pressure ratio cut-off values to improve diagnostic accuracy in the mid- and distal-LAD. (June 2021) - Balfe, C.; Jacob, B.; Hickey, N.; Moore, D.; Mulcahy, D.; Loo, B.
Highlights: This study assessed diastolic pressure ratio to FFR discordance. 12.7% of LAD lesions in this study had discordant result. 2.4% of non-LAD lesions had discordant results. This represents a statistically significant difference in discordance rate. Abstract: Previous studies have identified a higher rate of discordance between non-hyperaemic pressure ratios and FFR in the LAD when compared to the other two coronary arteries. We hypothesised that in keeping with recently published data, we would identify a higher discordance rate between diastolic pressure ratio (DPR) and FFR in the LAD compared to the RCA or LCx. In our study, 12.7% of LAD lesions had discordant results compared with 2.4% of non-LAD lesions. This represents a statistically significant increased rate of discordance in LAD lesions compared to non-LAD lesions (p = 0.04986). Note was made of a tendency for non-proximal LAD lesions to be associated with false-positive DPR results in the borderline range (0.88 and 0.89). In a speculative, hypothesis generating post-hoc analysis, we found an improved diagnostic accuracy of DPR when the cut-off value for a positive DPR in the non-proximal LAD was changed to ≤0.87. It is fathomable that improvements in the diagnostic accuracy of DPR for FFR may be improved by tailoring DPR cut-offs to the location of the lesion assessed.